Moral Authority of Procedure and Recidivism: Reassessing the Limits of Restorative Justice in Criminal Law - Dwi Belqis Apriliarista Devi; Alfons Zakaria (CV. Dyoqu Publishing and Management, 2025)
Abstrak Background: Restorative justice is intended to repair harm and offer a credible alternative to routine punitive responses, yet its practice is often narrowed by procedural eligibility rules that come to be treated as the measure of justice itself. A recurring illustration is the blanket exclusion of repeat offenders from restorative pathways. Aims: This article re-examines whether recidivism should legitimately limit access to restorative justice, and asks whether such exclusions align with restorative aims or instead reflect a proceduralist bias that weakens equality before the law and victim-oriented resolution. Methods: Using a normative juridical design, the study combines statutory and conceptual approaches. It analyzes primary legal instruments governing restorative justice across the stages of investigation, prosecution, and adjudication, and reads them against doctrinal interpretation and key theoretical discussions on procedural justice, substantive justice, and restorative justice. Result: The findings suggest that recidivism-based restrictions frequently function as gatekeeping devices that privilege formal order and institutional convenience over contextual judgment about harm, accountability, and meaningful victim participation. As procedure is elevated into moral legitimacy, restorative justice risks being reduced to a compliance model, while the aims of reintegration and the prevention of recurrence receive limited space. Conclusion: Recidivism should not operate as an automatic disqualifier for restorative justice. A more principled framework would shift from rigid procedural exclusions to case-sensitive assessment centered on harm repair, responsibility, and social restoration.